Design Challenge in Management Education - Mirseyyedi, Simin (2010)
This is an exploratory study of the design challenges in business schools. It seeks to identify the most important design dimensions for management education and the management profession, with an aim of recommending a new business school in which students could obtain a variety of skills and abilities that will help them better face the complexity of the current business world.